DRIVING SUSTAINABLE BUSINESS GROWTH IN FINANCIAL STRATEGIES UD AGUS JAYA - Daniswara, Muhammad Daffa; Handayani, Sri (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
AbstractThe rice industry is a critical sector in Indonesia, facing challenges due to fluctuations in supply and demand that affect prices and availability. In 2023, the price of rice in Indonesia skyrocketed to Rp18,000 per kilogram. Many rice companies in Indonesia fail to provide their products in both modern and traditional markets due to supply limitations, resulting in decreased sales and profits. UD Agus Jaya is a prominent player in the rice industry. It was established in 1970 and is headquartered in Klaten, Central Java. The company endeavours to address the issue by expanding its operations. This study conducts a financial feasibility analysis of UD Agus Jaya to establish a new warehouse in West Java. This study utilizes internal company data and industry benchmarks to calculate the payback time, Net Present Value (NPV), and Internal Rate of Return (IRR). Analysis reveals that the proposed expansion is financially viable, with a payback period of 2 years, an NPV of IDR 2,260,642,028, and an IRR of 43%, which is much higher than the Weighted Average Cost of Capital (WACC) of 7.12%. This finding demonstrates that the strategic decision to build a new warehouse in West Java will enhance market reach, operational efficiency, and profitability for UD Agus Jaya. This study concludes that the strategy to build a new warehouse is not only feasible but also crucial for sustainable business growth, confirming that this investment is financially viable and beneficial for the long-term success of UD Agus Jaya.